Localized prostate cancer – high-dose conformal radiotherapy as one of treatment modality - Stryczyńska, Grażyna; Milecki, Piotr; Nawrocki, Sergiusz; Stachowski, Tomasz; Kwias, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2000)
The high-dose 3D conformal radiotherapy as one of treatment mode in the localized prostate cancer has been presented, since the generally accepted treatment strategy in this stage of disease has not been established yet. The technological advance in the quality of irradiation (calculating and delivery of dose in the target and organ at risks) that could be observed in the last few years together with introducing of a new 3D conformal radiation therapy may lead to significant therapeutic gain. The outcomes of treatment of the prostate cancer in early stage of disease (T1-2 N0 M0) by applying the high-dose conformal three dimensional radiotherapy (3D CRT) alone are comparable to radical prostatectomy. In the group of patients who refused surgery, radiotherapy is only radical mode of treatment. In advanced stage of disease (T3-4 N0 M0) combined radiotherapy with hormonotherapy may increase the survival of patients. The postoperative radiotherapy in the group of patients with high risk of local recurrence (pT2/3N0M0) also improves outcomes of the treatment.